2015
DOI: 10.1016/j.btre.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Screening of cyanobacteria and microalgae for their ability to synthesize silver nanoparticles with antibacterial activity

Abstract: The aim of this study was to assess the ability of selected strains of cyanobacteria and microalgae to biosynthesize silver nanoparticles (Ag-NPs) by using two procedures; (i) suspending the live and washed biomass of microalgae and cyanobacteria into the AgNO3 solution and (ii) by adding AgNO3 into a cell-free culture liquid. Ag-NPs were biosynthesized by 14 out of 16 tested strains. In most of the cases Ag-NPs were formed both in the presence of biomass as well as in the cell-free culture liquid. This indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
169
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(189 citation statements)
references
References 42 publications
5
169
0
2
Order By: Relevance
“…32,33 Bekasova et al 34 demonstrated the synthesis of AgNPs using RPE extracted from the red alga Callithamnion rubosum. Our data are consistent with these publications suggesting that phycobiliproteins are able to reduce PdCl 2 .…”
Section: Results and Discussion Synthesis And Characterization Of Pdnpsmentioning
confidence: 99%
“…32,33 Bekasova et al 34 demonstrated the synthesis of AgNPs using RPE extracted from the red alga Callithamnion rubosum. Our data are consistent with these publications suggesting that phycobiliproteins are able to reduce PdCl 2 .…”
Section: Results and Discussion Synthesis And Characterization Of Pdnpsmentioning
confidence: 99%
“…The biosynthesis of nanoparticles via marine algae and other marine plants is a new and emerging research field. Several studies have shown these biological entities to have the potential to produce a wide range of metal and metal oxide nanoparticles using ecofriendly methods [118,119]. The following sections summarize and discuss currently available literature reports that have investigated a number of marine algae.…”
Section: Types Of Nanoparticles Produced By Marine Algae and Marine Pmentioning
confidence: 99%
“…Por otra parte para la fabricación biológica de NPs es posible utilizar cultivos de bacterias o cianobacterias (Patel et al, 2015), hongos (Ahmad et al, 2003), microalgas (Patel et al, 2015) o bien cultivos de células u órganos vegetales (AlShalabi y Doran 2013), plantas completas (Mittal et al, 2014) o sus estructuras, por ejemplo brotes (Gardea-Torresdey et al 2003), flores y tallos (Kuppusamy et al, 2016) o raíces (Pardha-Saradhi et al, 2014b). El proceso de fabricación biológica puede ocurrir de forma intracelular (Haverkamp and Marshall 2008), extracelular (Li et al, 2011) o inclusive ex planta por medio de los exudados radicales (Pardha-Saradhi et al, 2014a).…”
Section: Nanoparticles Biomanufacturingunclassified
“…Moreover for biological production of NPs can use cultures of bacteria or cyanobacteria (Patel et al, 2015), fungi (Ahmad et al, 2003), microalgae (Patel et al, 2015) or cell cultures or plant organs (Al-Shalabi and Doran 2013), whole plants (Mittal et al, 2014) or structures such outbreaks (Gardea-Torresdey et al, 2003), flowers and stems (Kuppusamy et al, 2014) or roots (PardhaSaradhi et al, 2014b). The manufacturing process may occur biological intracellularly (Haverkamp and Marshall 2008), extracellular (Li et al, 2011) or even ex plant via root exudates (Pardha-Saradhi et al, 2014A).…”
Section: Nanoparticles Biomanufacturingmentioning
confidence: 99%